The prison system and its effects - Taylor, Antony (Criminal justice, law enforcement and corrections, 2011)
Introduction -- Consensus of informed opinion about the need for change -- Prison overcrowding -- Conceptualizing the prison as a social system -- Assessing the general effects of imprisonment adverse reactions to imprisonment -- The management of captives -- The development of prisons in New Zealand -- Recent official inquiries into the New Zealand prison system -- Overview and conclusions